Applying the consumption values theory to explain farmers’ choice of interest–free agriculture financing products - Imran Mehboob Shaikh (Emerald Group Publishing Limited, 2024)
Purpose – Using the consumption values theory (CVT) as a baseline model, this study aims to evaluate the factors that influence farmers’ decision-making behavior regarding interest-free agricultural financing products. Design/methodology/approach – Data were gathered from 321 banking customers using questionnaires who are engaged with the agriculture sector and wish to obtain finance related to Islamic agriculture products. Findings – The findings demonstrate that the decision behavior for Islamic agriculture financing products is highly influenced by epistemic, emotional and functional values. On the contrary, conditional and social values do not influence farmers’ choice behavior for Islamic agriculture financing products. Research limitations/implications – There are a few limitations in this study. Initially, the study’s geographic scope is limited to bank customers within the agriculture sector who live, in particular, in Southern Sindh province, Pakistan. Next, researchers extended the CVT to a specific focus on agricultural financing products by Islamic banks. Future researchers should take these concerns into consideration for better applicability, and it is anticipated that the research approach will be refined to best expand the results. Lastly, future researchers are expected to broaden the theory’s relevance by considering the socio-cultural environmental conditions (culture, religious values and approaches) and social conditions in a wider range of Islamic agricultural financial instruments. Practical implications – The findings are beneficial for practitioners intending to advance innovative Islamic agriculture financing products to cater to Pakistani farmers’ needs. Originality/value – This research extends the CVT that offers valuable information for the development of consumers’ behavior in the setting of interest-free agricultural financing